Suppressing the Antibody Response with Siglec Ligands - Nitschke, Lars (New England Journal of Medicine, 2013)
Production of antibodies to self-antigens is a risk factor for autoimmune disease. A potential strategy to suppress production of specific antibodies by B cells may involve stimulation of a class of repressor receptors, the sialic acid-binding immunoglobulin-like lectins. When stimulated by antigens, B cells produce antibodies a crucial response against pathogens and the basis of all successful vaccines. The dark side of this immune response is that it can be directed against self-antigens, potentially resulting in autoimmune disease. Autoreactive B cells are largely eliminated in the bone marrow, but some escape the bone marrow and are found in the periphery as polyreactive or autoreactive B cells. However, a second mechanism guards against autoimmune mayhem: inhibitory receptors expressed on the surface of B cells for example, the sialic acid-binding immunoglobulin-like lectins (Siglecs) prevent autoimmune reactions. Macauley ...